Is an extended alloplastic replacement (eTMJR) device an option for the management of mandibular defects involving the temporomandibular joint? - A prospective cohort study - Sabine S. Linsen; Marcus Teschke; Frederick Far; Louis G. Mercuri (Elsevier, 2024)
The reconstruction of large mandibular deficits involving the temporomandibular joint (TMJ) can be challenging. Extended alloplastic total temporomandibular joint reconstruction (eTMJR) is one treatment option.This single center, prospective, long-term observational study evaluates the objective and subjective outcomes of 21 eTMJR subjects followed >5 years postoperatively. The long-term stability of the eTMJR was determined by collecting objective data (mandibular kinematics, contralateral surface electromyography (sEMG), maximum voluntary clenching (MVC)) and subjective oral health related quality of life (oHrQoL).Except for mandibular deviation on opening, the objective variables markedly improved. A statistically significant decrease was found for ipsilateral condylar hypermobility (P = 0.001), and an increase in bilateral MVC (ipsilateral P = 0.029, contralateral P = 0.015). The subjective outcomes 'diet consistency' (P = 0.001) and 'physical distress' (P = 0.043) improved significantly.Based on the stability of the eTMJR devices over the study period, improved objective and subjective variables, eTMJR appears to be a safe and effective predictable management option for patients with large mandibular deficits including the TMJ.